Social Factors Linking Stigma‐Related Stress with Alcohol Use among Lesbians. (21st September 2017) - Lewis, Robin J.; Winstead, Barbara A.; Lau‐Barraco, Cathy; Mason, Tyler B.
Abstract: A conceptual model linking stigma‐related stress and lesbian women's alcohol use and related problems via social factors (i.e., social constraints and social isolation), depressive symptoms, and negative reinforcement drinking motives (i.e., coping and conformity) was tested. Self‐identified lesbian women ( N = 1, 048), age 18–35 years in the United States completed an online survey of discrimination, stigma consciousness, social isolation, social constraints, depressive symptoms, drinking motives, alcohol use, and related problems. The hypothesized path model showed excellent model fit. The predicted pathway of stigma‐related stressors to alcohol outcomes via social factors, depressive symptoms, and coping/conformity motives was largely supported. Results highlight the importance of social factors in linking stigma‐related stress to alcohol use and related problems among lesbians. Understanding the underlying social mechanisms connecting stigma to negative health outcomes may help inform intervention efforts to reduce alcohol use and related problems among lesbians and associated health disparities.